A Distracted Muse: The Positive Effect of Dual-Task Distraction on Creative Potential. Issue 4 (1st October 2020) - Collins, Maurice James D'Arcy
ABSTRACT: Where do novel ideas come from? What mental processes facilitate them? The disinhibition hypothesis suggests creative cognition can be assisted by reducing cognitive inhibition of ideas, facilitating looser associative thoughts to bond with one another to produce novel concepts. Past exploration of the disinhibition hypothesis has been drawn from neuroatypical populations, examining the effects of substances, mood, or distraction tasks to overcome cognitive fixation on a single idea. This study explored the disinhibition hypothesis effect on divergent thinking (a measure of creative potential), in a neurotypical population of post-graduate students (n = 50; f = 31; mean age = 24), via a dual-task distraction task (the Simon Task) designed to occupy participants' inhibitory attention. Unlike past work, the present dual-task design enables clarification of whether it is the distraction that facilitates creative responses, or whether the latter are merely an effect of the passage of time between being presented with a problem and offering a solution. Further, the repeated measures design facilitates querying to what degree this form of cognition is environmentally malleable. Participants significantly improved across all four metrics of divergent thinking (fluency; flexibility; originality; elaboration) under dual-task distraction conditions, with a large effect observed for total score improvement.